1998
DOI: 10.1007/s000240050127
|View full text |Cite
|
Sign up to set email alerts
|

Regional Correlation Analysis between Seismic Heterogeneity in the Lower Mantle and Subduction in the Last 180 Myr: Implications for Mantle Dynamics and Rheology

Abstract: We have carried out a regional correlation analysis between the seismic structure of the lower mantle and the reconstructions of subduction sites in the past 180 Myr with the aim of estimating individual styles of slab motion over different parts of the earth. The correlation patterns obtained for three subduction branches (West Pacific, East Pacific and Alpine-Himalayan) are remarkably different. In the West Pacific, the subducting slabs tend to be stagnant beneath the 660-km discontinuity, while basically no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…We have, however, found that fast anomalies are imaged consistently in the midmantle where we would expect slabs in the absence of a long‐term barrier to flow at 660 km (Figures 14 and 17). This substantiates previous studies [ van der Hilst et al , 1997; Čížková et al , 1998; Bunge et al , 1998], and slab penetration is found to be a common phenomenon (Figure 18). As discussed, it can be expected that future flow models will do a better job in predicting slab locations and current discrepancies should lead to a better understanding of the nature of the subduction process.…”
Section: Discussionsupporting
confidence: 93%
“…We have, however, found that fast anomalies are imaged consistently in the midmantle where we would expect slabs in the absence of a long‐term barrier to flow at 660 km (Figures 14 and 17). This substantiates previous studies [ van der Hilst et al , 1997; Čížková et al , 1998; Bunge et al , 1998], and slab penetration is found to be a common phenomenon (Figure 18). As discussed, it can be expected that future flow models will do a better job in predicting slab locations and current discrepancies should lead to a better understanding of the nature of the subduction process.…”
Section: Discussionsupporting
confidence: 93%